Psikoedukasi Peningkatan Penerimaan Orang Tua Terhadap Anak Penyandang Disabilitas Melalui Pola Asuh Positif: Psychoeducation on Enhancing Parental Acceptance of Children with Disabilities through Positive Parenting - Elisa Dwi Anggraeni; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Parents of children with disabilities frequently encounter psychological challenges that affect acceptance and caregiving practices. Specific Background: Limited parental understanding of positive parenting principles was identified at SLB Aisyiyah Porong through a preliminary community need assessment, indicating the necessity of structured psychoeducational intervention. Knowledge Gap: Although positive parenting and parental acceptance have been widely discussed, empirical evidence based on structured psychoeducation targeting parents of children with disabilities in this specific context remains limited. Aims: This study aimed to examine changes in parental understanding following a positive parenting psychoeducation program. Results: Using a pre-experimental one-group pre-test and post-test design involving parents of children with disabilities, statistical analysis with paired sample t-test revealed a significant increase in post-test scores compared to pre-test results, indicating improved understanding after the intervention. Novelty: This study provides contextual empirical evidence of positive parenting psychoeducation implemented within a special education school setting using structured assessment and statistical evaluation. Implications: The findings support the integration of systematic psychoeducation programs in special schools to strengthen parental awareness and acceptance in raising children with disabilities, contributing to family-based developmental support practices. Keywords: Positive Parenting, Parental Acceptance, Psychoeducation, Children with Disabilities, Pre Experimental Design Key Findings Highlights: Structured educational sessions led to measurable score improvement between pretest and posttest. Statistical testing confirmed significant change after intervention delivery. Program implementation within special school context demonstrated contextual feasibility.